2020
DOI: 10.25073/2588-1132/vnumps.4267
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Antioxidant and α-glucosidase Inhibitory Activities of Codonopsisjavanica (Blume) Hook. f. Thoms’ Root Extract

Abstract: This study aims to evaluate the antioxidant ability and α-glucosidase inhibitory activities of Codonopsisjavanica extract to elucidate its mechanism in the treatment of diabetes type 2. The roots of Codonopsisjavanica were extracted with ethanol solvents and fractionated with n-hexane, ethyl acetate and butanol solvents. The total extract and the fractions were evaluated for free radical scavenging by 2.2-diphenyl-1-picrylhydrazyl method and α-glucosidase inhibitory activity in vitro. The study results show th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
0
0
1
Order By: Relevance
“…This clearly indicates that plant extracts have the potential to manage hyperglycemia. 6,21,30,33,34 Similar to the studies by Bhati et al on Cornus capitata 5 and Nguyen et al on Codonopsis javanica, 4 the ethyl acetate fraction was found to possess the strongest enzyme inhibitory activity among extracts. Moreover, Le et al evaluated the antithrombotic activity of the aerial part of CG and reported that the ethyl acetate fraction had more substantial antiplatelet and anticoagulant activities than other fractions.…”
Section: Total Flavonoid Contentsupporting
confidence: 79%
See 1 more Smart Citation
“…This clearly indicates that plant extracts have the potential to manage hyperglycemia. 6,21,30,33,34 Similar to the studies by Bhati et al on Cornus capitata 5 and Nguyen et al on Codonopsis javanica, 4 the ethyl acetate fraction was found to possess the strongest enzyme inhibitory activity among extracts. Moreover, Le et al evaluated the antithrombotic activity of the aerial part of CG and reported that the ethyl acetate fraction had more substantial antiplatelet and anticoagulant activities than other fractions.…”
Section: Total Flavonoid Contentsupporting
confidence: 79%
“…Screening inhibitors of α-amylase and α-glucosidase from medicinal plants has received much attention. [3][4][5][6][7] Canna x generalis L.H Bailey & E.Z Bailey (CG) is a medicinal plant belonging to the Canna genus. In traditional medicine, Canna plants have been commonly used to treat various conditions such as diarrhea, hepatitis, dysentery, gonorrhea, bruises, pain, and heart diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Các nghiên cứu đã chỉ ra rằng các chiết xuất thực vật có khả năng kiểm soát tình trạng tăng đường huyết [2,13,14]. Tương tự kết quả nghiên cứu của Bhati và cộng sự trên loài Cornus capitata [15] và nghiên cứu của Nguyễn Thị Thuý và cộng sự trên loài Codonopsisjavanica [16], nghiên cứu này cũng cho thấy phân đoạn ethyl acetate thể hiện hoạt tính ức chế enzyme mạnh nhất so với cao chiết tổng và các phân đoạn khác. Ngoài ra, nghiên cứu trước đây về hoạt tính chống huyết khối của phần trên mặt đất của CG đã báo cáo rằng cao chiết phân đoạn ethyl acetate có hoạt tính chống ngưng tập tiểu cầu, chống đông máu và chống oxy hoá mạnh hơn so với các phân đoạn khác [5].…”
Section: Bàn Luậnunclassified